FRI0345 Autoantibodies in Rheumatoid Arthritis Specifically Recognize Igg Heavy Chain Complexed with Hla-Dr, Which is Strongly Associated with Rheumatoid Arthritis Susceptibility. (10th June 2014) - Jin, H.; Arase, N.; Hirayasu, K.; Kohyama, M.; Suenaga, T.; Saito, F.; Tanimura, K.; Matsuoka, S.; Ebina, K.; Shi, K.; Yasuda, S.; Horita, T.; et al.
Abstract : Background: Particular HLA class II alleles are strongly associated with susceptibility to rheumatoid arthritis; however, how HLA class II molecules regulate susceptibility to autoimmune diseases has remained unclear. Rheumatoid factor (RF) is an autoantibody that binds to denatured IgG or Fc fragments of IgG, and is detected in about 80% of rheumatoid arthritis (RA) patients, but also in 5-10% of healthy individuals as well as in other autoimmune diseases. However, the natural antigens that are recognized by RF are unknown. On the other hand, we have recently found that HLA class II molecules function as a molecular chaperon to transport cellular misfolded proteins to the cell surface (1). Objectives: We addressed whether misfolded or structurally altered IgG heavy chain (IgGH) transported to the cell surface by HLA class II molecules of particular HLA-DR alleles are targets for autoantibodies in RA. Methods: Binding of autoantibodies from RA patients (n=112) to IgGH transported to the cell surface by HLA class II molecules of various HLA-DR alleles was analyzed by flow cytometry. In situ association of IgGH with HLA class II molecules in paraffin-embedded tissue sections from RA patients was analyzed by proximity ligation assay. Results: Intact IgGH was transported to the cell surface by HLA class II molecules via association with the peptide-binding groove of HLA class II molecules. The IgGH complexed with HLA class II molecules were specifically recognized by autoantibodies in RF-positive sera from RA patients. In contrast, autoantibodies in RF-positive sera from non-RA individuals did not bind to IgGH/HLA-DR complexes (Fig. 1A ). Furthermore, a strong correlation between autoantibody binding to IgG complexed with certain HLA-DR alleles and the odds ratio for that allele's association with RA was observed (r=0.81, P =4.6x10 -5 ) (Fig. 1B ). In situ association of autoantigens with HLA class II molecules was detected in autoimmune diseased tissues but not in control tissues. Similar autoantibody binding to misfolded proteins complexed with HLA class II molecules was observed in other autoimmune diseases. Conclusions: IgGH complexed with HLA class II molecules is a specific target for autoantibodies in RA. Strong correlation between RA-susceptibility conferred by each HLA-DR allele and autoantibody binding to IgGH complexed with HLA class II molecules suggests that such protein complexes might be involved in pathogenesis of RA. Our findings suggest that misfolded proteins complexed with HLA class II molecules are novel candidates for diagnostic and therapeutic targets in autoimmune diseases. References: Jiang, Y., Arase, N., Kohyama, M., Hirayasu, K., Suenaga, T., Jin, H., Matsumoto, M., Shida, K., L. Lanier, L., Saito, T. & Arase, H. (2013) Transport of misfolded endoplasmic reticulum proteins to the cell surface by MHC class II molecules. Int. Immunol. 25:235-246. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4810